Strategies of Algerian Media Campaigns in Raising Traffic Awareness - Mokhtar DJELLOULI & Brahim DJENNAD (Akofena)
Abstract: Algeria is witnessing a significant increase in traffic accidents, causing substantial human and material losses that exceed 300 billion dinars annually, according to security and national gendarmerie statistics. In response to this crisis, authorities have intensified preventive measures, such as enhancing security surveillance, installing monitoring cameras, and enacting stricter laws. This study aims to explore the role of media campaigns in raising public awareness about the dangers of traffic accidents and the extent to which the media contributes to building a traffic culture. The findings indicate that media campaigns, alongside strict security measures, help reduce accidents and promote adherence to traffic laws. However, their success requires coordinated efforts between security authorities and media outlets to achieve a lasting impact. Keywords: Strategy, Media campaign, Traffic awareness, Algerian media.